Synthesis and Investigation of the Properties of Polymer-immobilized Silver- and Gold Nanoparticles - Burkeyev, M.Zh.; Shibayeva, S.R.; Khamitova, T.O.; Plocek, Jiri; Nurmaganbetova, M.T.; Kazhmuratova, A.T.; Zhumagalieva, T.S. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Metal–polymer composites (MPC) based on copolymers of polypropylene glycol maleate phthalate with acrylic acid and metallic gold and silver were synthesized for the first time. The structure of nanocomposites is characterized with the help of microscopy and spectroscopy. Antimicrobial activity of novel metal-polymeric complexes based on silver and gold was studied. Metal-polymeric complexes were stabilized for the first time with polymeric matrix based on the copolymers of polypropyleneglycolmaleatephthalate with acrylic acid (p-PGMPh/AA:Ag, p-PGMPh/AA:Au). Obtained nanocomposites contain the nanoparticles of silver and gold of rhomboidal and cylindrical shapes with the sizes of 40–50 and 35–50 nm correspondingly. The size of more than 80 % of the nanoparticles are from 20 to 50 nm and has a spherical and rhombic shape. For determination of antimicrobial activity of the MPC the reference test-microorganisms such as facultative-anaerobe gram-positive Staphylococcus aureus, aerobic gram-positive spore-forming Bacillus subtilis, gram-negative facultative anaerobe of Escheriсhia coli, aerobic Pseudomonas aeruginosa and yeast fungi Сandida albicans have been used. The resulting nanocomposites are stable and promising for the creation of new pho-tochromic and nonlinear optical materials, as well as for using in medicine in the development of antiseptic and antimicrobial materials that are needed during a pandemic.
Күміс пен алтын полимер-иммобилизацияланған нанобөлшектерінің синтезі және олардың қасиеттерін зерттеу
Синтез и исследование свойств полимер-иммобилизованных наночастиц серебра и золота
Keywords: nanocomposites; nanoparticles; silver; gold; copolymer; polypropylene glycol maleate phthalate with acrylic acid; metal–polymer complex; antimicrobial activity